2019
DOI: 10.1590/1679-78255191
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-order strategy for meshless solution of plate bending problems with the generalized finite difference method

Abstract: This paper presents some recent advances on the numerical solution of the classical Germain-Lagrange equation for plate bending of thin elastic plates. A meshless strategy using the Generalized Finite Difference Method (GFDM) is proposed upon substitution of the original fourth-order differential equation by a system composed of two second-order partial differential equations. Mixed boundary conditions, variable nodal density and curved contours are some of the explored aspects. Simulations using very dense cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To account for the elastic Winkler foundation, k W h 4 /D is added to the term associated to the node of interest in the stencil describing the governing equations (Equations (8e), (9g), (10), and ( 11)). Equation (8e) i.e.…”
Section: Elastic Winkler Foundation Over An Area Of the Platementioning
confidence: 99%
See 1 more Smart Citation
“…To account for the elastic Winkler foundation, k W h 4 /D is added to the term associated to the node of interest in the stencil describing the governing equations (Equations (8e), (9g), (10), and ( 11)). Equation (8e) i.e.…”
Section: Elastic Winkler Foundation Over An Area Of the Platementioning
confidence: 99%
“…the governing equations and constrained boundary conditions were derived based on the first-order shear deformation theory and Hamilton's principle. Ferreira et al [10] proposed a meshless strategy using the Generalized Finite Difference Method upon substitution of the original fourth-order differential equation by a system composed of two second-order partial differential equations; mixed boundary conditions, variable nodal density and curved contours were explored.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that for each point of the discretization, the approximate values of the derivatives depend only on three factors: the number of points of the star, the arrangement of the points around the central point and the weighting function, as can be seen in Equation (12). It is in Equation (13) where the ODE comes into play. The strategy that we propose uses techniques that are already known and used to improve the approximation of the derivatives, but instead of applying them to the whole discretization, we do it selectively in the conflictive points.…”
Section: F I G U R E Formation Of Global Vector Gmentioning
confidence: 99%
“…The use of second-order approximations with the GFDM has received attention in the last two decades and has been successfully consolidated. Its applications vary among many types of problems, such us: seismic wave propagation, 7 hyperbolic nonlinear equations, 8 transient heat flow in anisotropic composites, 9 mathematical models of tumor growth, 10 inverse heat conduction problem, 11 discontinuous crack-faces, 12 plate bending problems, 13 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thai, H. T et al [39] developed an analytical solution for refined plate. Ferreira et al [40] presented a meshless strategy using the Generalized Finite Difference Method (GFDM) for plate bending problems. They showed that by using this method, the original fourth-order differential equation could be substituted by a system composed of two second-order partial differential equations.…”
Section: Introductionmentioning
confidence: 99%